Answer:
3
Step-by-step explanation:
3*4/4
4/4 is equal to 1
3*1
3
Answer:
x = ± 2
Step-by-step explanation:
Given
x² + 5 = 3x² - 3 ( subtract x² + 5 from both sides )
0 = 2x² - 8 ( add 8 to both sides )
8 = 2x² ( divide both sides by 2 )
4 = x² ( take the square root of both sides )
x = ±
= ± 2
Answer:
(5/12)d - (23/36)g
Step-by-step explanation:
First you can eliminate g and -g to get (1/6)d - (3/4)g + (1/9)g + (1/4)d. Then you need to get common denominators to add like terms together.
1/6 = 4/24 and 1/4 = 6/24. Add them together to get (10/24)d or (5/12)d.
-3/4 = -27/36 and 1/9 = 4/36. Add them together to get (-23/36)g.
So in standard form, (5/12)d - (23/36)g
Answer:
15
Step-by-step explanation:
Okay, so we know that Base*Length=Area, so we just have to divide the area by the base, so the formula here is Area/Base=Length.
That would get us 120/8=Length,
and if we just divide 120 by 8 we get 15, so the length is 15
Y=x2 the extreme would be x=0